Hydrothermal synthesis of CuO/functionalized graphene nanocomposites for dye degradation - Yusoff, N.; Huang , N.M.; Muhamad, M.R.; Kumar, S.V.; Lim, H.N.; Harrison, I. (2012)
Copper oxide (CuO) had been successfully decorated on functionalized graphene (FG) sheets using a simple hydrothermal technique. Functionalized graphene oxide (FGO) was used instead of GO as the starting material for the successful preparation of nanocomposites. A series of nanocomposites with varying amounts of FGO was prepared to study the morphological changes of CuO crystals on the FG sheets. X-ray Diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM) confirmed the formation of the nanocomposites. The nanocomposite exhibited good catalytic activity towards the degradation of methylene blue (MB). The catalytic performance was improved with the increasing amount of FG due to the enhanced synergy interaction between CuO and FG.